Two Years of Cinacalcet Hydrochloride Treatment Decreased Parathyroid Gland Volume and Serum Parathyroid Hormone Level in Hemodialysis Patients With Advanced Secondary Hyperparathyroidism. Issue 4 (7th April 2015) - Yamada, Shunsuke; Tokumoto, Masanori; Taniguchi, Masatomo; Toyonaga, Jiro; Suehiro, Takaichi; Eriguchi, Rieko; Fujimi, Satoru; Ooboshi, Hiroaki; Kitazono, Takanari; Tsuruya, Kazuhiko
Abstract The long‐term effect of cinacalcet hydrochloride treatment on parathyroid gland (PTG) volume has been scarcely investigated in patients with moderate to advanced secondary hyperparathyroidism (SHPT). The present study was a prospective observational study to determine the effect of cinacalcet treatment on PTG volume and serum biochemical parameters in 60 patients with renal SHPT, already treated with intravenous vitamin D receptor activator (VDRA). Measurement of biochemical parameters and PTG volumes were performed periodically, which were analyzed by stratification into tertiles across the baseline parathyroid hormone (PTH) level or PTG volume. We also determined the factors that can estimate the changes in PTG volume and the achievement of the target PTH range by multivariable analyses. Two years of cinacalcet treatment significantly decreased the serum levels of PTH, calcium, and phosphate, followed by the improvement of achieving the target ranges for these parameters recommended by the Japanese Society for Dialysis Therapy. Cinacalcet decreased the maximal and total PTG volume by about 30%, and also decreased the serum PTH level independent of the baseline serum PTH level and PTG volume. Ten out of 60 patients showed 30% increase in maximal PTG after 2 years. Multivariable analysis showed that patients with nodular PTG at baseline and patients with higher serum calcium and PTH levels at 1 year were likely to exceed the target range of PTH at two years. In conclusion, cinacalcet treatment with intravenous VDRA therapy decreased both PTG volume and serum intact PTH level, irrespective of the pretreatment PTG status and past treatment history.